Non-communicable diseases in the world over the past century: a secondary data analysis - Taheri Soodejani, Moslem (Frontiers in Public Health, 2024)
We visualized the change in the top 10 non-communicable diseases (NCDs) in the recent century by the World Health Organization (WHO) regions.The data were extracted from Global Burden of Disease (GBD) studies. After we accessed this source, all NCDs were sorted according to their prevalence in 2019, and the 10 most common NCDs were selected. Then, the incidence, prevalence, and death rate of these 10 NCDs were compared with the rates in 2000.Diabetes and kidney disease had the highest increase in incidence (49.4%) and prevalence (28%) in the Eastern Mediterranean region. Substance use disorders had a huge increase (138%) in the death rate among women in the Americas region. On the other region, women in South-East Asia experienced the greatest decrease in incidence (-19.8 %), prevalence (-15.8 %), and death (-66%).Almost all NCDs have increased in recent years; the death rate has still declined in all regions. Lifestyle can be a major cause of this increase, but health and medical services such as screening and treatment help with survival.